2020
DOI: 10.13102/sociobiology.v67i2.4895
|View full text |Cite
|
Sign up to set email alerts
|

Ants (Hymenoptera: Formicidae) as surrogates for epigeic arthropods in Northern Andalusian ‘dehesas’ (Spain)

Abstract: The ‘dehesas’ are important and vast agro-silvo-pastoral systems typical of the Iberian Peninsula that are undergoing a crisis due to their low economic profitability and environmental degradation. Thus, it is necessary to identify effective tools that provide a reliable idea of the status of these ecosystems as a starting point for future measures of conservation. In this study we analyse the possible role of ants as surrogates for epigeic arthropods, a common biodiversity indicator group. A total of 15 farms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In terms of ant community composition, the one encountered in the 18 years-excluded site differed from those found in the grazed one, with ant community assemblages sharing a similar ant community composition to the findings by Jiménez-Carmona et al (2020) in an analogous Mediterranean woodland. The measurement of ant functional structure and diversity allowed us to better understand ant biodiversity responses along the post-grazing succession.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In terms of ant community composition, the one encountered in the 18 years-excluded site differed from those found in the grazed one, with ant community assemblages sharing a similar ant community composition to the findings by Jiménez-Carmona et al (2020) in an analogous Mediterranean woodland. The measurement of ant functional structure and diversity allowed us to better understand ant biodiversity responses along the post-grazing succession.…”
Section: Discussionmentioning
confidence: 59%
“…they mediate soil turnover, seed dispersal, nutrient cycling and pest control among others (Offenberg 2015). Changes in ant community composition and functional traits have been linked with different land use practices and because their sensitivity towards environmental changes is high, and their response to disturbance and restoration efforts is quick and measurable, they are often used as ecological indicators to monitor post-disturbance changes (Ottonetti et al 2006;Dahms et al 2010;Ellison 2012;Tiede et al 2017;Jiménez-Carmona et al, 2020). Disturbances, such as fire and deforestation and changes in land-use, such as plantations, may have severe consequences for the soil-plant interface, where most grounddwelling ants live and forage (Vasconcelos et al 2017;Martello et al 2018;de Queiroz et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, in the present century, studies on several taxonomic groups have demonstrated that the heterogeneity of spatial habitats, resulting in a wide variety of habitats and microhabitats inhabiting wood pastures, improves the overall diversity at the landscape level. Moreno et al [29] highlighted the importance of microhabitats and marginal habitats on plants, bees, spiders, and earthworms, and Jiménez-Carmona et al [83] did likewise for ants. Farms with different microhabitat types (i.e., linear features, temporary water courses, scrub patches, and traditional stone walls) showed an increased number of species, since unique species were found in every habitat type and contributed to the overall diversity.…”
Section: Habitat Heterogeneitymentioning
confidence: 99%